2008
DOI: 10.1007/s11668-008-9119-8
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Acoustic Emission for Estimation of Bearing Defect Size

Abstract: Vibration monitoring of rolling element bearings is possibly the most established diagnostic technique for rotating machinery. The application of Acoustic Emission (AE) for bearing diagnosis is gaining ground as a complementary diagnostic tool, however, limitations in the successful application of the AE technique have been partly due to the difficulty in processing, interpreting and classifying the acquired data. Furthermore, the extent of bearing damage has eluded the AE diagnostician. The investigation repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…Despite of the success of vibration-based methodologies, over the last decades bearing condition monitoring techniques based on Acoustic Emission (AE) have become very popular [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. AE has demonstrated to be a very powerful tool for fault detection and diagnosis particularly in bearings, and some recent studies [13; 32; 33] reported that AE can be more sensitive in detecting incipient faults in bearings over other methodologies based on vibration data.…”
Section: Condition Monitoring Of Bearings Based On Acoustic Emissionmentioning
confidence: 99%
“…Despite of the success of vibration-based methodologies, over the last decades bearing condition monitoring techniques based on Acoustic Emission (AE) have become very popular [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. AE has demonstrated to be a very powerful tool for fault detection and diagnosis particularly in bearings, and some recent studies [13; 32; 33] reported that AE can be more sensitive in detecting incipient faults in bearings over other methodologies based on vibration data.…”
Section: Condition Monitoring Of Bearings Based On Acoustic Emissionmentioning
confidence: 99%
“…The high sensitivity of AE technique and AE parameters in detecting the incipient bearing faults has become one of the significant advantages of AE over vibration measurement. 3 A comprehensive review of AE application for bearing fault detection was presented by Mba et al 4 Al-Ghamd et al 5,6 investigated the relationship between AE parameters in time domain and defect size. They concluded that AE burst duration is an effective parameter for identifying defect size on the outer race.…”
Section: Introductionmentioning
confidence: 99%
“…4 Al-Ghamd et al. 5,6 investigated the relationship between AE parameters in time domain and defect size. They concluded that AE burst duration is an effective parameter for identifying defect size on the outer race.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] AE techniques have numerous advantages over vibrationbased approaches. Namely, AE techniques are capable of incipient fault detection.…”
Section: Introductionmentioning
confidence: 99%